2021
DOI: 10.1111/ppe.12800
|View full text |Cite
|
Sign up to set email alerts
|

Time trends, geographic variation and risk factors for gastroschisis in Canada: A population‐based cohort study 2006–2017

Abstract: Background Previous studies showed increases in rates of gastroschisis in Canada in the first decade of the 21st century. Objective We sought to examine the epidemiologic characteristics of gastroschisis in Canada in recent years. Methods We conducted a retrospective population‐based cohort study of all livebirths and stillbirths delivered in Canada (excluding Quebec) from 2006 to 2017, with information obtained from the Canadian Institute for Health Information. Gastroschisis rates by maternal age, region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
(104 reference statements)
0
17
0
3
Order By: Relevance
“…Analyses of other data sets have yielded a wide range of effect estimates associated with alcohol consumption treating maternal age as a confounder rather than an effect modifier. Studies from California 9 and Canada 35 observed estimates similar to those from NBDPS (ORs 1.6–1.7), while others report protective effects (OR 0.8) 11 as well as ORs well above null (OR 15.1) 17 . Many studies rely on administrative exposure data 9,17,35 and differences in alcohol consumption measurement makes it difficult to compare results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of other data sets have yielded a wide range of effect estimates associated with alcohol consumption treating maternal age as a confounder rather than an effect modifier. Studies from California 9 and Canada 35 observed estimates similar to those from NBDPS (ORs 1.6–1.7), while others report protective effects (OR 0.8) 11 as well as ORs well above null (OR 15.1) 17 . Many studies rely on administrative exposure data 9,17,35 and differences in alcohol consumption measurement makes it difficult to compare results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from California 9 and Canada 35 observed estimates similar to those from NBDPS (ORs 1.6–1.7), while others report protective effects (OR 0.8) 11 as well as ORs well above null (OR 15.1) 17 . Many studies rely on administrative exposure data 9,17,35 and differences in alcohol consumption measurement makes it difficult to compare results. However one age‐matched case‐control study in Brazil used a modified version of the NBDPS questionnaire and reported a moderately strong association between periconceptional alcohol consumption and gastroschisis (OR 2.6) 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our secondary analysis of gestational diabetes by conception season may also elucidate the inverse associations of gastroschisis with gestational diabetes observed in previous studies. 9,24,25 However, several limitations must be noted. Firstly, some risk factors that are associated with gastroschisis may be tested after the occurrence of a congenital anomaly or other adverse pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported a signi cantly increasing temporal trend in the maternal age-adjusted rate, and identi ed maternal hypothyroidism, substance use and northern residence as signi cant risk factors for gastroschisis in Canada. 9 A recent study of global gastroschisis patterns among 23 countries showed an extremely wide range in the prevalence for teen women (< 20 years): from 2.1 in Slovak Republic or 3.7 per 10 000 births in Spain to 21.5 in Utah (U.S) and 26.2 per 10 000 in Canada. 3 However, researchers have paid little attention to why gastroschisis varies with location (e.g., northern area) of residence and the complex relationship and interplay between maternal characteristics, conditions and identi ed risk factors, as well as the mechanistic pathway.…”
Section: Introductionmentioning
confidence: 99%